KEBIJAKAN PEMERINTAH TENTANG PENYEDIAAN SARANA DAN PRASARANA OLAHRAGA DI KABUPATEN LOMBOK TIMUR PROVINSI NUSA TENGGARA BARAT (Analisis Tentang Perencanaan, Realisasi, Pengelolaan dan Pemanfaatan Sarana dan Prasarana Olahraga) - Muhsan Muhsan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2017)
Local Government plays an important part in the attempt of promoting sport, through developing Local Regulation or other policies governing planning, realization, management and utilization of sport infrastructure. The objective of research was to find the truth about planning, realization, management and utilization of sport infrastructure in Lombok Timur (East Lombok) Regency of Nusa Tenggara Barat (West Nusa Tenggara) Province. The method employed in this research was descriptive qualitative one with snowball sampling approach. The subject of research was government policy about sport infrastructure provision, and then the data source of research constituted the document of local regulation or other policies the local government had developed about sport obtained from direct observation, document and archive study, and interview with informant, in this case the Chief of Youth and Sport Division, Chief of Second Commission of Local Legislative Assembly (DPRD), Chief of Legislation Sub Division and Daily Chief of KONI for Lombok Timur. The result obtained in this research was elaborated as follows. 1) The planning of sport infrastructure provision existing in Lombok Timur Regency was based on the public’s recommendation and also derived from Local Government proposing the Village’s sport infrastructure to Central Government. 2) The realization of sport infrastructure provision was still concentrated in Regency Capital only and had not been distributed evenly to each village or sub district existing in Lombok Timur Regency. 3) The management of sport infrastructure existing in Lombok Timur Regency had not been maximal due to unclear fund source for maintenance leading many preexisting sport infrastructure to be neglected and damaged. 4) The utilization of preexisting sport infrastructure in Lombok Timur Regency was less maximal because it was often used for other certain activities than sport activity. Thus, it could be concluded in this research that the Local Government policy about Sport Infrastructure developed by Local Government of Lombok Timur Regency had not been felt evenly by all levels of society, because the provision of sport infrastructure was still concentrated around the Capital of Regency only.